Christological Program in the Apse of Basilica Eufrasiana in Poreč - Vicelja-Matijašić, Marina (IKON, 2008)
Abstract The rich and ambiguous wall mosaic decoration of the cathedral in Poreč has been interpreted in various ways revealing its complex content of the imagery. Especially interesting are the images in the main apse which are the subject of this article. The earlier interpretations were focused on the imagery and meaning of Theotokos considering Poreč mosaic to be one of the earliest complete representation of Virgin’s role as the Mother of God connected with growing devotion towards the Virgin within the Byzantine empire and its capital. Recently, more accent is given to the different layers of messages – public and private – conveyed within images. But, despite the fact that the iconography of the mosaics is multivalent, as is the case with other decorations of the 6th century, the main feature of the program is the visualization of Christological themes in reference to the basic doctrines of the period. Also, this text examines the question in what extent did and could Christological disputes of the time influence visual programs of the church decoration in the 6th century with the specific issue on the possible and repeatedly mentioned role of the Three Chapters controversy in the framing of the Poreč’ mosaics.